2010
DOI: 10.1097/rhu.0b013e3181c78ddc
|View full text |Cite
|
Sign up to set email alerts
|

Refractory Polyarticular Gouty Arthritis as a Manifestation of Immune Reconstitution Inflammatory Syndrome

Abstract: Immune reconstitution inflammatory syndrome (IRIS) describes the initial clinical deterioration some patients manifest upon initiation of effective antiretroviral therapy (ART) for HIV infection. In this report we describe a case of IRIS manifesting as polyarticular gout, a previously unreported rheumatological manifestation of IRIS. A 53-year-old HIV-infected man with a history of intermittent attacks of gout and an initial CD4 count of 112 cells/microL and a viral load of >100,000 copies/mL presented to our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…The present case shares resemblance to the previously reported patient who presented with polyarticular gouty arthritis as a manifestation of IRIS 9 . In contrast to the case reported by SEBENY et al 9 , our patient had no prior history of gout and presented with monoarticular disease.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The present case shares resemblance to the previously reported patient who presented with polyarticular gouty arthritis as a manifestation of IRIS 9 . In contrast to the case reported by SEBENY et al 9 , our patient had no prior history of gout and presented with monoarticular disease.…”
Section: Discussionsupporting
confidence: 81%
“…The present case shares resemblance to the previously reported patient who presented with polyarticular gouty arthritis as a manifestation of IRIS 9 . In contrast to the case reported by SEBENY et al 9 , our patient had no prior history of gout and presented with monoarticular disease. Interestingly, he presented a relentless acute gout syndrome associated with exquisite pain that lasted three months and went on to develop signs of a draining tophus, which is uncommon in patients without prior signs and symptoms of gout.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…PMN cells are known to play a deleterious role in the acute phase of arthritic conditions such as RA and refractory gout [27,28]. Once in the joint, they produce reactive oxygen species and cytokines, thus contributing to an ongoing state of inflammation in the joint and joint destruction [29,30,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…5 In addition, there have been a number of case reports published. [6][7][8][9][10][11] Observational studies that have estimated the prevalence of gout in their HIV-positive patients have reported rates ranging between 0.4% in Nigeria 12 and 1% among patients attending a tertiary referral centre in India. 13 One UK study investigating the risk of infectious diseases among people with gout found that 0.1% of people with gout in the Clinical Practice Research Datalink (a large representative primary care database) had co-existent HIV.…”
Section: Introductionmentioning
confidence: 99%